Success Rate of Thorax Ultrasonography in Assisting Thoracocentesis Action in Clinical Pulmonary Tuberculosis at Respira Lung Hospital Yogyakarta - Siham Reifqie Fath; Sudiyono Sudiyono; Rini Indrati; Tri Asih Budiati; Gatot Murti Wibowo (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
The use of X-ray Thorax (XCR Thorax) in assisting thoracocentesis procedures has some limitations. XCR Thorax only provides a two-dimensional image, which may limit the accuracy in determining the exact location for the puncture. In addition, XCR Thorax cannot detect septation or loculation which may affect the success of the thoracocentesis procedure. Thoracic ultrasonography offers advantages in detecting pleural effusion compared to conventional radiographic methods, but has not been standardized in national guidelines. This study aims to see the difference in the success rate of thoracocentesis between the use of thoracic ultrasound guidance and thoracic photo guidance in patients with clinical tuberculosis at Respira Lung Hospital Yogyakarta. This cross-sectional study used a static group comparison approach to compare the success rate of thoracocentesis between two groups at Respira Lung Hospital Yogyakarta: 30 patients with Thorax ultrasound and Thorax photo guidance (Group A) and 30 patients only with Thorax photo guidance (Group B). With a purposive sampling method and analysis using the chi-square test, this study aims to analyze differences in the success rate of thoracocentesis in real clinical conditions without intervening in existing procedures in the hospital. Thoracocentesis with thorax photo plus thorax ultrasound guidance showed a success rate of 100% compared to 66.67% in procedures with thorax X-ray alone (p < 0.001). The results showed that the use of thoracic ultrasound as a thoracocentesis guide had a higher success rate compared to the use of thoracic photo guidance.